2012
DOI: 10.1167/iovs.11-9064
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Activity of Aganirsen in Nonhuman Primate and Rodent Models of Retinal Neovascular Disease after Topical Administration

Abstract: PURPOSE.Aganirsen, an antisense oligonucleotide inhibiting insulin receptor substrate (IRS)-1 expression, has been shown to promote the regression of pathologic corneal neovascularization in patients. In this study, the authors aimed to demonstrate the antiangiogenic activity of aganirsen in animal models of retinal neovascularization. METHODS. Eyedrops of aganirsen were applied daily in nonhuman primates after laser-induced choroidal neovascularization (CNV; model of wet age-related macular degeneration [AMD]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…Due to the above unmet needs, the potential for inhibition of CNV through topically delivered drugs has been examined previously (Kiuchi et al, 2008; Sheu et al, 2009; Cloutier et al, 2012; Birke et al, 2013). In our studies, we found an approximate 45% reduction in CNV when 1nmol (8.5μg) of AS1411 was applied once daily one day prior and 7 days post-laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the above unmet needs, the potential for inhibition of CNV through topically delivered drugs has been examined previously (Kiuchi et al, 2008; Sheu et al, 2009; Cloutier et al, 2012; Birke et al, 2013). In our studies, we found an approximate 45% reduction in CNV when 1nmol (8.5μg) of AS1411 was applied once daily one day prior and 7 days post-laser treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2, A and B). It has been suggested that the impaired barrier function of psoriatic lesions (Schittek, 2011) and the amphipathic nature of aganirsen (Cloutier et al, 2012) could facilitate uptake of antisense drugs in general and aganirsen in particular. In agreement, topical applications of aganirsen decreased psoriatic plaque area in both groups of patients (0.86 and 1.72 mg/g) compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, because both angiogenesis and inflammation are involved in the development of psoriasis, we speculated that aganirsen (GS-101) could be efficient in psoriatic patients. Aganirsen is an antisense oligonucleotide that inhibits the expression of insulin receptor substrate-1 (IRS-1) and has antiangiogenic activities, including inhibition of both VEGF and IL-1b expression (Andrieu-Soler et al, 2005;Al-Mahmood et al, 2009;Cloutier et al, 2012). In this study, we show that, by inhibiting IRS-1 expression in the cytoplasmic compartment, aganirsen impaired 14-3-3b-tristetraprolin protein (TTP) complex formation, leading to the inhibition of the expression of several cytokines with AU-rich mRNA, including , and TNFa.…”
Section: Introductionmentioning
confidence: 99%
“…Aganirsen will be the first therapeutic that will be approved for the topical treatment of corneal neovascularization. Since Aganirsen eye drops in primate models also reached sufficient levels at the retina and choroidea, Aganirsen also holds great promise for novel topical treatment options against AMD and retinal vascular diseases [92].…”
Section: Clinically Available Anti(lymph)angiogenic Agentsmentioning
confidence: 99%